The Implementation of Strategic Management in The Wilayatul Hisbah Institution in Enforcing Islamic Sharia - Chysara, Daris Iqbal; Trisnawati, Carni; PS, Aida Karimah (Islam Transformatif : Journal of Islamic Studies, 2024)
Abstract Aceh is a region that has the authority to regulate and implement Sharia by-law as a local government. The Islamic Sharia in Aceh is carried out by the Wilayatul Hisbah institution as a special authority that ensures the implementation of Islamic Sharia as it should be. As a government institution, Wilayatul Hisbah itself applies organizational management, particularly in strategy. This study aims to find out and understand how the formulation of the Wilayatul Hisbah strategy in Banda Aceh City in the Enforcement of Islamic Law, to know the implementation of the Wilayatul Hisbah strategy in Banda Aceh City, and to know the evaluation of strategies carried out by the Wilayatul Hisbah Institution of Banda Aceh City which is oriented towards the enforcement of Islamic law in Banda Aceh. The research method used is a descriptive method with a qualitative approach. The findings of this article reveal thatthe formulation and implementation carried out by the Wilayatul Hisbah institution of Banda Aceh City has been carried out following the basic values of strategic management governance, which takes into account long-term, medium-term, and short-term strategies outlined in the institution's Strategic Plan and the applicable Standard Operating Procedures, and in accordance with the principles of equality and justice. Abstrak Aceh adalah wilayah yang diberi kewenangan untuk mengatur dan menerapkan hukum sesuai dengan hukum Islam dalam kehidupan pemerintahannya sendiri. syariat Islam di Aceh dijalankan oleh Lembaga Wilayatul Hisbah sebagai otoritas khusus yang memastikan syariat Islam berjalan dengan sebagaimana mestinya, sebagai lembaga pemerintahan, Wilayatul Hisbah sendiri menerapkan manajemen organisasi, terkhusus dalam aspek strategi. Penelitian ini bertujuan untuk mengetahui dan memahami bagaimana perumusan strategi Wilayatul Hisbah di Kota Banda Aceh dalam Penegakan Hukum Islam, mengetahui implementasi strategi Wilayatul Hisbah di Kota Banda Aceh, dan mengetahui evaluasi strategi yang dilakukan oleh Lembaga Wilayatul Hisbah Kota Banda Aceh yang berorientasi pada penegakan hukum Islam di Banda Aceh. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif berdasarkan hasil analisis yang didapatkan, perumusan dan implementasi yang dilakukan oleh Lembaga Wilayatul Hisbah Kota Banda Aceh telah dilaksanakan sesuai dengan nilai-nilai dasar tata kelola manajemen strategis yang memperhitungkan strategi jangka panjang, jangka menengah, dan jangka pendek yang tertuang dalam Rencana Strategis lembaga dan Standar Operasional Prosedur yang berlaku, dan sesuai dengan asas kesetaraan dan keadilan.